2016
DOI: 10.1007/s00408-016-9957-1
|View full text |Cite
|
Sign up to set email alerts
|

Overnight Changes in Lung Function of Obese Patients with Obstructive Sleep Apnoea

Abstract: Purpose Obstructive sleep apnoea (OSA) is a prevalent disorder, characterised by collapse of the upper airways during sleep. The impact of sleep-disordered breathing on pulmonary function indices is however currently not well described. The aim of the study was to evaluate diurnal change in lung function indices in a cohort of patients with OSA and relate pulmonary function changes to disease severity. Methods 42 patients with OSA and 73 healthy control subjects participated in the study. Asthma and COPD were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
(51 reference statements)
2
23
0
Order By: Relevance
“…Disrupted sleep is a major component in the pathophysiology of OSA. Still, the number of studies investigating inflammatory biomarkers before and after night is low (Bikov et al, 2017;Jordan et al, 2005;Kunos et al, 2015;Mills, Natarajan, Von Kanel, Ancoli-Israel, & Dimsdale, 2009;Nobili et al, 2000). In contrast to the findings on CRP (Mills et al, 2009), we did not find an overnight change in C3a or SC5b-9 in the OSA or control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disrupted sleep is a major component in the pathophysiology of OSA. Still, the number of studies investigating inflammatory biomarkers before and after night is low (Bikov et al, 2017;Jordan et al, 2005;Kunos et al, 2015;Mills, Natarajan, Von Kanel, Ancoli-Israel, & Dimsdale, 2009;Nobili et al, 2000). In contrast to the findings on CRP (Mills et al, 2009), we did not find an overnight change in C3a or SC5b-9 in the OSA or control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnography was performed as it was described previously (Bikov et al, 2017;Kunos et al, 2015Kunos et al, , 2017 using Somnoscreen Plus Tele PSG (Somnomedics GmbH Germany). Electroencephalogram, electrooculogram and electromyogram, thoracic and abdominal respiratory excursions, breath sounds, nasal airflow, electrocardiogram and oxygen saturation were recorded according to guidelines (Kushida et al, 2005).…”
Section: Polysomnographymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the incidence of OSA is not clear as our study did not monitor the sleep for all COPD patients. It is well known that OSA is common in obese population and FEV 1 was reported to increase overnight in OSA patients with obesity (20). However, the mean BMI of COPD patients enrolled in this study was only 23.…”
Section: Copd Symptoms and Medicationmentioning
confidence: 65%
“…The PFT can also provide information on the lower respiratory tract, which may be involved in the pathogenesis of upper airway disease. Other studies also suggested that there are associations between OSA and intrathoracic airways [10][11][12].…”
mentioning
confidence: 95%